Necrotizing Enterocolitis: Synbiotics, Probiotics, and Prebiotics Prevention - Aziri, Zirly Vera; Manafe, Carolina Janicca Winda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Necrotizing Enterocolitis (NEC) or intestinal inflammation is a gastrointestinal disease that is the leading cause of death among infants. NEC is often diagnosed late due to its non-specific signs and symptoms, resulting in increased mortality and morbidity. The purpose of this paper is to explain the mechanisms of how synbiotics, probiotics, and prebiotics contribute to the prevention of NEC. Several randomized trials and observational studies have identified various factors associated with NEC. However, the causality of many of these factors remains unclear and may involve different etiological mechanisms. Prevention of NEC can be achieved through the administration of synbiotics, probiotics, and prebiotics. According to previous research, the administration of synbiotics, probiotics, and prebiotics has significant potential and benefits in preventing NEC. The data sources were obtained by conducting an online search through library databases, including PubMed, ProQuest, ScienceDirect, MDPI, and Google Scholar. According to previous research, the administration of synbiotics, probiotics, and prebiotics has significant potential and benefits in preventing NEC. This paper summarizes the current etiology, risk factors and synbiotics, probiotics, and prebiotics Prevention of Necrotizing Enterocolitis.